LncRNA PAPPA-AS1 Induces the Development of Hypertrophic Scar by Upregulating TLR4 through Interacting with TAF15. (5th July 2021) - Fan, Pengju; Wang, Yongjie; Li, Jingjing; Fang, Man
Abstract : Hypertrophic scar (HTS) is a complicated pathological process induced mainly by burns and wounds, with abnormal proliferation of fibroblasts and the transformation of fibroblasts to myofibroblasts. PAPPA-AS1, a differentially expressed long noncoding RNA (lncRNA) in the HTS tissues, attracted our interests in its potential role and mechanism in the development and process of HTS. In the present study, the regulatory effect of lncRNA PAPPA-AS1 on the Toll-like receptor 4 (TLR4) signal pathway, as well as the molecular mechanism, was investigated. Bioinformatics analysis was utilized to screen the differentially expressed lncRNAs in HTS tissues. PAPPA-AS1 was significantly upregulated in both HTS tissues and hypertrophic scar fibroblast (HTsFb) cells. The expression levels of TLR4, MyD88, TGF- β 1, collagen I, collagen III, and α -SMA were greatly elevated in HTsFb cells. By knocking down PAPPA-AS1, the proliferation of HTsFb cells, TLR4, and TGF- β 1 signal pathway and the expression of fibrosis markers both in HTsFb cells and HTS tissues were suppressed. It was accompanied by the alleviated pathological state in the HTS tissues, which were significantly reversed by cotransfecting with the pcDNA3.1-TLR4 vector. Positive correlation and interaction were observed between PAPPA-AS1 and TAF15 and between TAF15 and the promoter of TLR4, respectively. In conclusion, lncRNA PAPPA-AS1 might induce the development of HTS by upregulating TLR4 through interacting with TAF15.